Some Peircean approaches to organizational communication. Formal and informal relations in a museum - González Pérez, Carlos Federico (2014)
The main objectives of this work point to an analysis of internal communication processes of a natural science museum of the city of La Plata (Buenos Aires province) to explain the relationship between the formal and informal instances from some ap¬proaches to the Peircean semiotics perspective. Other experiences are also taken into account in order to consider different ways of museum´s materialization. We believe that the contribution of this semiotic view is enriching because of its triadic sign scheme and because it allows to regard nonlinear complex processes related to the cultural aspects of museums, determined by a given historical moment. The research in the theoretical directions of the authors who are included in this perspective, enables us to approach the complexity of communication processes, given that all communication is done through signs, and signs can be interpreted in one or another way and can grow and generate a more developed set of signs. We resort to specific operations of visual image semiotics to analyze the signaling in museums, and to specific operations of symbolic semiotics to analyze the discourse of interviews. Through these operations we can achieve explanations about what kind of valuation does the museum´s stuff perform about the formal communication pro-cesses and also as to the informal spaces which complement them. We can also state that some problems in the organizational structure must be resolved (as an important segmentation identified in the named museum) in order to implement a participative communication model. We identify some aspects related to extension strategies, to the studies of public, and to the relationship that the museum at study has with Argentine aboriginal communities, and likewise aspects that the organization values in the present and wants to project into the future.